Health Education of Mother and Child to Reduce Prevalence of Stunting in Medokan Semampir Surabaya - Taufiqurrahman Sidqi; Eny Inayati; Ario Imandiri (Darmabakti Cendekia: Journal of Community Service and Engagements, 2019)
Background: Stunting is a chronic nutritional problem in infants characterized by a length or height that is lacking compared to age. The prevalence of stunting in Medokan Semampir Village was 30.48% while the WHO standard states that free stunting if it is less than 20%. Purpose: This activity aims to provide knowledge and skills to mothers who will and already have a toddler to prevent stunting in RW 02 Medokan Semampir. Methods: This program was implemented in 4 steps those are planning, acting, observing, and evaluating. Results: The results of the health examination for toddlers who participated in the activity showed that there were no cases of stunting, but there were 3 toddlers who were underweight, so it needed to be increasingly inadequate nutrition. Whereas the mother’s examination showed 6 people who had low Hb levels and 2 people had high blood sugar levels. Toddler massage training provides the skills of mothers who had toddlers and toddler cadres in RW 02 to take independent action on their babies. Balanced nutrition counseling, exclusive breastfeeding, and mandatory immunization rose participant awareness in efforts to prevent stunting. Whereas the socialization of dental and oral health provided knowledge on how to clean the teeth of mothers and toddlers correctly and safely to avoid dental caries which can cause stunting in toddlers. Conclusion: This program was very useful for mothers and toddlers because it provides knowledge and skills in efforts to prevent the incidence of stunting toddlers.